Note from the editor - Schutte, Corne (The South African Journal of Industrial Engineering, 2018)
“Companies have too many experts who block innovation. True innovation really comes from perpendicular thinking.” - Peter Diamandis We are yet again finalising the first edition of 2018, and the rest of 2018 promises to be an exciting one again: SAIIE is organising its annual conference in October, and as in the 2 previous years, we plan to continue with a special edition in 2018, where the best contributions in the conference, identified during the peer review process, is selected for the Special Edition. This edition has a total of 16 articles, with 12 from authors with South African connections and the balance from international authors. The feature article in this edition leverages a mathematical model of innovation for complex adaptive systems to explore organisational innovation investigations conducted at Stanford University Medical Center, with an aim to allow additional sources of innovation. If you have suggestions on how we can take this journal forward, please let me know. C.S.L. Schutte: Editor